The Relationship between Perceived Benefits/Barriers of Self-care Behaviors and Self Management in Diabetic Patients - Morowatisharifabad MA; Rouhani Tonekaboni N (Tehran University of Medical Sciences, 2007)
Background & Aim: Diabetes is the most common disease due to metabolism disorder with long term complications. Self-care is a basic factor in control of the disease. If diabetic patients perceive the benefits of self-care behaviors, then the perceived barriers will decrease(net benefit)  and the likelihood of engaging in self-care behaviors will increase. This study was carried out with the aim of determining perceived benefits/barriers to self-care behaviors and it's relation with practicing self-care behaviors among diabetic patients referred to Yazd diabetes research center.Methods & Materials: This is a cross-sectional study. Study subjects (n=120) were selected among patients referred to Yazd diabetes research center. Data were collected using a two-section questionnaire. The first section was to assess demographic characteristics of the subjects and the second section was to assess perceived benefits and barriers and self care behaviors constructs. Results: Perceived benefits score among the patients was 88 per cent and perceived barriers score was 27.75 per cent. Self-care behavior was done by 62.79 per cent of the patients. There was a significant relationship between perceived benefits and diabetes duration. Perceived benefits was also positively correlated with self care behaviors (P=0.01). There was also a negative correlation between perceived barriers and self-care behaviors (P=0.01). Net benefit also had a direct correlation with self-care behavior with P=0.01. Perceived benefits and perceived barriers also had a negative correlation with each other with P=0.01. Perceived benefits and barriers accounted for 28.2 percent variance of self-care behaviors.Conclusion: Perceiving benefits of self-care behaviors by diabetic patients will cause an increase on practicing self-care behaviors and this will be more possible if the barriers to self-care behaviors be minimized. Therefore, for promotion of diabetic patients' quality of life, attention to these important factors is recommended.